Pengembangan Musik Google Sites “PELAN: 4KM” untuk Pembelajaran Sifat Kepemimpinan Khulafaur Rasyidin Kelas 5 SD - Nafisa Eka Septiningsih; Mila Nurhanifa Rani; Maylani Tria Putri (ANWARUL, 2026)
Although the development of digital learning media in Islamic Religious Education has been widely carried out, studies that specifically integrate Google Sites-based animated music videos for learning the leadership qualities of the Khulafaur Rasyidin in elementary schools remain limited. This study aims to develop and test the feasibility of the Google Sites learning media “PELAN: 4 KM” (Pemimpin Teladan: 4 Khalifah Mulia) on the topic of the leadership qualities of the Khulafaur Rasyidin for Grade 5 elementary school students. This study used a descriptive qualitative approach with a Design and Development Research (D&D) design through the ADDIE development model. The study involved 20 Grade 5 students of SD Negeri Cikoneng I, one material expert, and one media expert. Data were collected through observation, questionnaires, interviews, and documentation, then analyzed descriptively. The results showed that the “PELAN: 4 KM” media obtained a very good category from the material expert and media expert and received positive responses from students. The media, which combines animated music videos, digital materials, and interactive quizzes, was able to increase learning interest and facilitate students’ understanding of the Khulafaur Rasyidin material. The conclusion of this study affirms that the integration of animated music videos and Google Sites is feasible for use as an interactive, meaningful, and enjoyable Islamic Religious Education learning medium. These findings contribute to the development of multimedia learning media based on digital technology in Islamic Religious Education and open opportunities for further research to test the effectiveness of the media on a broader sample through an experimental design. Keywords: Google Sites; Animated Music Videos; Khulafaur Rasyidin; Islamic Religious Education; Digital Learning Media